2005
DOI: 10.1002/rcm.2023
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐15 in NO characterises differently reactive soil organic N pools

Abstract: Intercropping with legumes is known to increase the plant-available nitrogen (N) in soil, but can also increase leaching of NO3- to the groundwater. To minimise NO3- leaching risks, knowledge of the N-release processes is essential, including an estimate of the contribution of legumes to total NO3- concentrations in soil. Our objectives were to answer the questions: (1) whether the presence of legume roots increases N mineralisation, and (2) whether the proportion of legume-derived N in NO3- could be calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Sand ecosystems in general are characterised by relatively low amounts of organic soil compounds, high water permeability and, therefore, a comparatively low storage capacity for water and nutrients (Scheffer & Schachtschabel 2002). Thus, the fraction of mineralised N that is washed into the groundwater (Oelmann et al. 2005) is particularly high in these systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand ecosystems in general are characterised by relatively low amounts of organic soil compounds, high water permeability and, therefore, a comparatively low storage capacity for water and nutrients (Scheffer & Schachtschabel 2002). Thus, the fraction of mineralised N that is washed into the groundwater (Oelmann et al. 2005) is particularly high in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Sand ecosystems in general are characterised by relatively low amounts of organic soil compounds, high water permeability and, therefore, a comparatively low storage capacity for water and nutrients (Scheffer & Schachtschabel 2002). Thus, the fraction of mineralised N that is washed into the groundwater (Oelmann et al 2005) is particularly high in these systems. Further, it is well known that drought and highsoil temperatures, both common events in open grassland ecosystems on sand, lower N 2 fixation efficiency (Carranca et al 1999;Serraj et al 1999;Zahran 1999;Valles de la Mora et al 2003) and thus reduce the speed of succession (Vitousek et al 2002).…”
Section: The Relative Importance Of N 2 -Fixing Legumesmentioning
confidence: 99%
“…The model was based on two labile organic N pools derived from litter of the tree and grass, and a recalcitrant organic N pool in the soil. According to these authors 15 N fractionation during mineralization could be estimated from the 15 N content of the total organic N and the mineral N obtained from laboratory or field incubation experiments (Natelhoffer and Fry, 1988;Oelmann et al, 2005), or from the 15 N content of the total organic N of different soil layers (Vervaet et al, 2002). Model simulations duplicated well the observed relationships between organic N, mineralized N, their 15 N content and apparent 15 N fractionation, the latter varying from þ1.2 to þ2.4‰.…”
Section: Isotopic Fractionationmentioning
confidence: 99%
“…Stable isotope abundances of N have been used extensively to provide information on the origins and transformations of N in soils, surface waters and ground waters 3–9. It has also been demonstrated by a number of studies that a wide variety of chemical and biological processes (i.e.…”
mentioning
confidence: 99%
“…Taken alone, however, δ 15 N values fail to distinguish among the various N sources due to overlapping ranges and though isotopic fractionations which occur during N transformations. Further studies have suggested that the oxygen (O) isotope content of NO 3 may provide additional information on microbial processes, such as denitrification,12 as well as better distinguishing the sources of NO 3 in waters, particularly discrimination between atmospheric, microbial and synthetic fertiliser NO 3 8, 13–19. Hence, one can expect that a dual isotope approach with respect to the identification of NO 3 sources may provide more reliable information with respect to the NO 3 sources and biogeochemical interactions during NO 3 production.…”
mentioning
confidence: 99%